Implementing E-Learning for Increasing Studentâs Motivation in Learning English - Saefurrohman, Saefurrohman; Istikharoh, Lutfi (ASPENSI, 2012)
ABSTRACT: This study was aimed to find out the influence of E-learning for improving studentsâ motivation in learning English. The subject of the study was the third semester students of English Department who have a different social background of study, mostly from middle social class and suburb school. The writers applied Classroom Action Research (CAR) as a method of the study. The writers also conducted the CAR since preparation phase, planning, action, observation, and reflection. The data were collected through observation, interview, questionnaire, and documentation. The result of this research showed that the studentsâ motivation increased from the beginning of the study to the end of it (50% improvement). The students found easy way in accessing material using E-learning, so that they were able to practice their communication both in written and spoken forms by using it. Finally, they were also motivated in learning English. KEY WORD: E-learning, English students, motivation, classroom action research, and teaching-learning process.IKHTISAR: Penelitian ini bertujuan untuk meningkatkan motivasi mahasiswa dalam belajar Bahasa Inggris dengan menggunakan E-learning. Subjek dari penelitian ini adalah mahasiswa semester 3 pendidikan Bahasa Inggris yang berasal dari latar belakang yang berbeda, dan sebagian besar berasal dari daerah pedesaan. Penulis menggunakan Penelitian Tindakan Kelas (PTK) sebagai metode dalam penelitian ini. Penulis melakukan tahapan PTK dari mulai perencanaan, pelaksanaan, observasi, dan refleksi. Data dikumpulkan melalui observasi, wawancara, angket, dan dokumentasi. Hasil penelitian ini menunjukkan bahwa motivasi belajar mahasiswa meningkat dari awal penelitian hingga akhir (peningkatannya sebesar 50%). Mahasiswa juga mudah dalam mengakses berbagai sumber dengan menggunakan E-learning, sehingga mereka dapat mempraktekkan Bahasa Inggris, lisan dan tertulis, dengan baik dan penuh antusias. Akhirnya, mereka juga nampak bahwa motivasi mereka dalam belajar Bahasa Inggris meningkat.KATA KUNCI: E-learning, mahasiswa bahasa Inggris, motivasi, penelitian tindakan kelas, dan proses belajar-mengajar.Â Â Â About the Authors: Saefurrohman, M.Pd. and Lutfi Istikharoh, M.Pd. are Lecturers at the Faculty of Education and Teacher Training UMP (Muhammadiyah University of Purwokerto), Jalan Raya Dukuhwaluh, Purwokerto City, Central Java, Indonesia. E-mail address: saefur19@gmail.comHow to cite this article? Saefurrohman & Lutfi Istikharoh. (2012). âImplementing E-Learning for Increasing Studentâs Motivation in Learning Englishâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.2(1) Juni, pp.67-78. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290.Chronicle of the article: Accepted (April 10, 2012); Revised (May 20, 2012); and Published (June 15, 2012).